2017
DOI: 10.18203/2394-6040.ijcmph20170752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of substance abuse among youth in Central Kerala, India

Abstract: Background: Substance abuse in various forms has been a social problem in various forms for many centuries. Kerala shows a high prevalence in alcoholism and is ranked top in India. This study is aimed at finding the prevalence and determinants of substance abuse among youth in central part of Kerala in South India.Methods: A community based study was done with 402 college student participants using a self- administered pretested semi structured questionnaire. Data was entered into microsoft excel and analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…Awareness regarding substance being harmful to health was observed in 90% of the students in our study which is comparable to 96% found in a study from Kerala. [ 26 ] The students reported being taught in the school about adverse effects of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness regarding substance being harmful to health was observed in 90% of the students in our study which is comparable to 96% found in a study from Kerala. [ 26 ] The students reported being taught in the school about adverse effects of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…Raphael et al in Kerala also reported significantly higher prevalence of substance abuse among males than females. 11 In our study, 25.6% of the participants reported having indulged in a physical fight and 12.5% reported having been bullied. Lesser number of adolescents reported having indulged in a physical fight in a study conducted by Sousa et al in Portugal (7.9%).…”
Section: Discussionmentioning
confidence: 45%
“…One study showed Level of knowledge on harmfulness of substance use among students was very high and they stated media as the most frequent source of information [15]. One Indian study showed that study material regarding substance abuse and their harmful effects can be imparted to teachers and later introduced in school curriculum [16].…”
Section: Discussionmentioning
confidence: 99%